Canada : Selected Issues. (IMF Staff Country Reports; Country Report, 1997)
This Selected Issues paper reviews Canada's business tax system, looking at the incentive effects of the country's business tax regime and their implications for output and employment. It presents estimates of marginal effective tax rates on corporate-source income in Canada and comparator countries across sectors, asset classes, means of finance, and asset ownership. The paper also examines labor markets in Canada. It notes that unemployment rates in Canada have risen across all demographic groups, industries, and regions, although young and less-educated workers and workers in agriculture and primary industries have been most severely affected.